Pantun Sebagai Media Penyalur Ekspresi Jiwa Siswa Kelas 7 Sekolah Menengah Pertama Negeri 3 Tugu Trenggalek - Fahrudin Fahrudin (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
Pantun as a medium for expressing the soul in social life is part of Malay culture. We remember that the influence of Malay culture which gave birth to the unified Indonesian language unwittingly gave birth to the character of a nation. The Malay community, which is also included in it, is the forerunner of Indonesian society, making it a reflection of the community's culture. It is important to know that by writing or creating rhymes, memory can be truly extraordinary. Cipta pantun provides enthusiasm by expressing various ideas that are still hidden in students' minds. Students at a young age are expected to achieve as expected by the school.